Multiple Mechanisms Driving F-actin-Dependent Transport of Organelles to and From Secretory Sites in Bovine Chromaffin Cells - Gimenez-Molina, Yolanda; Villanueva, José; Francés, Maria del Mar; Viniegra, Salvador; Gutiérrez, Luis M. (Frontiers in Cellular Neuroscience, 2018)
Neuroendocrine chromaffin cells represent an excellent model to study the molecular mechanisms associated with the exo-endocytotic cycle of neurotransmitter release. In this study, EGFP-Lifeact and confocal microscopy has been used to analyze the re-organization of the cortical F-actin cytoskeleton associated to organelle transport during secretion with unprecedented detail. In these cells secretory events accumulate in temperature-sensitive and myosin II-dependent F-actin expansions and retractions affecting specific regions of the sub-membrane space. Interestingly, not only vesicles but also mitochondria are transported towards the plasmalemma during these expansions. Simultaneously, we found F-actin cytoskeletal retraction withdraws vesicles from the sub-plasmalemmal space, forming novel empty internal spaces into which organelles can be transported. In addition to these well-coordinated, F-actin-myosin II dependent processes that drive the transport of the majority of vesicles, fast transport of chromaffin vesicles was observed, albeit less frequently, which used F-actin comet tails nucleated from the granular membrane. Thus, upon cell stimulation F-actin structures use diverse mechanisms to transport organelles to and from the membrane during the exo-endocytotic cycle taking place in specific areas of cell periphery.